The idea of governance in public policy as an inspiration for adults to learn cooperation. The example of Gdańsk migration policy - Beata Cyboran (Rocznik Andragogiczny, 2018)
Migration policy is a one of the public policies. In Poland, migration policy is very traditional. It does not change, like other public policies. It does not present idea of governance and community participation. This is one of the most difficult policies and should be based on modern social management. If society have the opportunity to decide about local migration policy, will be much less conflicts with immigrants. The governance concept has an educational potential. A good example, how to educate the local community for migrations, is a model of migrant integration, which is implemented in Gdańsk.